QUALITY CONTROL ANALYSIS WITH SQC (STATISTICAL QUALITY CONTROL) METHOD ON RAFT FOUNDATION WORK - Bagus Soebandono (Sean Institute, 2023)
It is necessary to control the quality of the concrete, so that the concrete specification requirements plan is achieved. The results of quality control research on PT